Avaliação do tratamento de um efluente de estabelecimento de apoio a saúde através de reator anaeróbio e processo oxidativo avançado - Sá, Roberson Davis (2021)
Wastewater from health care facilities is composed by several recalcitrant and toxic organic contaminants. These effluents are discharged into an effluent collection network, when it exists, for co-treatment in municipal wastewater treatment plants. In this sense, the combination of systems aimed at improving effluent quality and reducing toxicity is advantageous. Therefore, this work aims to evaluate the performance of hospital effluent treatment in the combination of the anaerobic system by a UASB reactor followed by advanced oxidation processes (AOPs). Also, the treatment of clinical analysis hospital laboratory wastewater by the AOP photo-Fenton at four distinct radiation settings. Both wastewaters were collected from a hospital with a tertiary level of health care. For this, in the first case, a UASB type reactor was operated in four stages. Stage I was operated with synthetic substrate (organic loading rate – OLR 0.6925 kg COD m-3d-1), Stage II was operated with synthetic effluent: hospital effluent 25:50 (v/v) with OLR 1.0733 kg COD m-3d-1. Stage III (synthetic effluent:hospital effluent 50:50, v/v) with OLR 1.4475 kg COD m-3d-1. Finally, Stage IV was operated strictly with hospital effluent (OLR 1.8781 kg COD m-3d-1). UVC-Vis photolysis and AOPs Fenton, photo-Fenton and UV-C/H2O2 were applied to samples of raw hospital effluent and as post-treatment of the effluent from the UASB reactor. The processes were carried out in a conventional bench scale photochemical reactor (500 mL). For the irradiated processes, a high-pressure mercury vapor lamp (125 W) with a quartz (UVC-Vis) or borosilicate glass (UVA-Vis) protective bulb was used. The clinical analysis hospital laboratory wastewater was submitted to the photo-Fenton process with the lamp suspended on the surface (13 cm) or with the lamp submerged, with UVA-Vis or UVC-Vis radiation. Bioassays were performed to determine the acute toxicity in Daphnia magna and phytotoxicity in Lactuca sativa seeds. The operation of the UASB reactor during the 4 stages demonstrated robustness of the anaerobic treatment. Biomass adaptation was observed, and in Stage IV the UASB reactor removed an average of 73(5)% of COD (average influent COD 1095 (129) mg O2 L-1). The samples before and after biological treatment showed toxicity to the organisms D. magna and L. sativa. For the post-treatment of the UASB reactor, the overall efficiency achieved in the UASB+photo-Fenton system was 90% (influent COD to the 1219 mg O2 L-1). However, samples after AOPs showed a toxic effect of inhibiting the growth of L. sativa seeds. Regarding the treatment clinical analysis hospital laboratory wastewater, the photo-Fenton process performed with a submerged lamp with UVAVis radiation showed the best results, reducing COD by 96% (COD decrease from 2365 to 104 mg O2 L-1). It was noted no toxic effect to the organisms of D. magna and L. sativa for this setting. In general, this work demonstrated the applicability of AOPs in hospital effluent matrices, both in isolation and in the combination UASB+AOP.